The Implementation Of Integrative Strategies In Teaching Maharah Qirā’ah: Challenges And Pedagogical Implications - Linur, Rahmat; Rusdi, Rusdi; Agung, Nur; Sandi, Aprilia (Jurnal Naskhi Jurnal Kajian Pendidikan dan Bahasa Arab, 2025)
This study aims to investigate the implementation of integrative strategies in teaching maharah qirā’ah at the Arabic Language and Literature Program at STAIN Madina. Reading skill plays a crucial role in Arabic language learning; however, students still face various difficulties, particularly in understanding vocabulary, identifying main ideas, and interpreting meanings contextually. Therefore, integrative strategies are considered a relevant approach to address these challenges by combining multiple instructional methods into a unified learning process. This study employed a qualitative descriptive approach with a case study design. The research participants consisted of lecturers and students involved in the teaching and learning process of maharah qirā’ah. Data were collected through classroom observations, in-depth interviews, and documentation, and were analyzed using an interactive data analysis model, which includes data reduction, data display, and conclusion drawing. Data validity was ensured through triangulation and member checking techniques. The findings indicate that the implementation of integrative strategies was carried out through vocabulary enrichment, contextual reading, collaborative discussion, and guided interpretation. This approach significantly improved students’ engagement, motivation, and participation in the learning process. In addition, students demonstrated improved abilities in reading comprehension, particularly in identifying main ideas, understanding vocabulary in context, and applying independent reading strategies. In conclusion, integrative strategies are an effective approach in teaching maharah qirā’ah as they create a more interactive, student-centered, and meaningful learning environment. These strategies not only enhance students’ reading abilities but also support the development of higher-order thinking skills